Intratonsillar Immunotherapy: A Convenient and Effective Alternative to Subcutaneous Immunotherapy for Allergic Rhinitis - Tian Gu; Wei Zhang; Lu Tan; Rong Xiang; Peiqiang Liu; Jingyu Huang; Qin Deng; Yuqin Deng; Zezhang Tao; Shiming Chen; Yu Xu (Research)
Allergen-specific immunotherapy (AIT) is the only treatment that addresses the root cause of immunoglobulin E (IgE)-mediated allergies, but conventional methods face challenges with treatment duration, patient compliance, and adverse effects. In this study, we propose intratonsillar immunotherapy (ITIT) as a new effective and safer route for AIT. Prior to clinical trials, we analyzed tonsil samples from human subjects to assess immune responses, measuring interleukin-4 (IL-4), IL-21, total IgE (tIgE), and allergen-specific IgE concentrations using ELISA and BioIC. Our results indicated that tonsils contained higher levels of allergen-specific IgE compared to peripheral blood. In the clinical phase, 120 allergic rhinitis (AR) patients were treated with either 3 intratonsillar allergen injections over 2 months or conventional subcutaneous immunotherapy (SCIT) over 1 year. ITIT demonstrated superior and faster symptom relief, especially in younger patients, while requiring markedly fewer doses and injections than SCIT. Immunological analysis revealed reduced eosinophil counts, increased regulatory T (Treg) and follicular regulatory T (TFR) cell levels, and a favorable shift in cytokine profiles. Adverse events were minimal, and the treatment showed high patient compliance. These findings suggest that ITIT could provide an effective, safer, and more convenient alternative to AIT.